Conceptual framework for analysing structural change in agriculture and rural livelihoods - Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2007)
The Deliverable 2.1 (D2.1) of the SCARLED project provides the conceptual framework for analysing structural change in agriculture and rural livelihoods in the NMS and established Member States of the EU. It concisely summarizes the underlying theories and concepts of the pertinent research issues in SCARLED. SCARLED addresses a topic of wide interest with regard to the identification of past and future key social and agricultural restructuring processes for a living countryside in the NMS. Methodologically, the topic is approached by comparative, structured multi-country farm surveys complemented by an analysis of structural changes in the farm sectors of two selected regions with the agent-based simulation model AgriPoliS, taking special account of demographic changes. In addition, SCARLED studies success stories of rural development in selected regions of five established Member States. For all topics covered by the SCARLED workpackages, the most relevant literature has been reviewed. The driving forces of structural change and rural livelihoods are identified and discussed in detail. All subsequent SCARLED analyses and methodological approaches will refer to this document. On the basis of this conceptual framework paper, the framework for the survey tool is established and will be further developed to serve the needs of the empirically based workpackages. The analysis of rural development success stories in established Member States will use the common methodological framework outlined in D2.1. The literature used in D2.1 is customized in Endnotes, a software system for managing bibliographies. Furthermore, it is noted that outputs and new developments in SCARLED will be documented on the project's homepage - www.scarled.eu.
urn:nbn:de:gbv:3:2-11426
Keywords: 330